Traveling butterflies - Shingū, Susumu, 1937- (Owlkids Books, 2015)
Monarch butterfly migration is one of nature's great mysteries. How do monarchs manage to fly some 2,500 miles from Canada and the northern United States south to Mexico? How do they trace a route they've never flown and reach the same destination their ancestors once found? Traveling Butterflies indulges the awe these creatures inspire by taking a poetic, meditative look at the monarch's life cycle. In a lyrical voice that seamlessly blends fact and storytelling, the book zooms in to show a monarch's progression from an egg the size of a dewdrop through growth, metamorphosis and preparation for their journey south. Rich illustrations in a vibrant color palette bring the butterflies to life and depict the rural and urban landscapes through which they fly. Rounded out with a page of factual text about monarchs and their migration, this informational picture book will leave readers equal parts informed and entranced. --Publisher.